1993
DOI: 10.3109/02844319309079788
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Laser Doppler Recordings from Free Flaps

Abstract: Although the transfer of free flaps is nowadays accomplished with an increasing degree of safety, thrombosis of the microvascular anastomoses is still a problem. In order to avoid delay in re-operating, various methods for objective blood flow monitoring have been tried, among them Laser Doppler Flowmetry (LDF). When one reviews the literature, it is apparent that opinions differ about whether or not LDF is a reliable technique for this purpose. To focus on the need to interpret continuous recordings, this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…This enables a depth-selective measuring of flow and velocity. Earlier studies criticized the lack of absolute values and difficulty in interpreting measured values because of high variability 5,29 . This difficulty can be limited through intra-individual values measured when the flap is raised.…”
Section: Discussionmentioning
confidence: 97%
“…This enables a depth-selective measuring of flow and velocity. Earlier studies criticized the lack of absolute values and difficulty in interpreting measured values because of high variability 5,29 . This difficulty can be limited through intra-individual values measured when the flap is raised.…”
Section: Discussionmentioning
confidence: 97%
“…Many authors have found this to be an objective, reproducible and non-invasive method which is accurate and reliable (Kind et al, 1998;Yuen and Feng, 2000). However, the recordings of laser Doppler flowmetry require careful interpretation (Svensson et al, 1993). Furthermore, there are some inherent limitations when it is used for monitoring free flaps.…”
Section: Discussionmentioning
confidence: 98%
“…Klinische Parameter wie die Rekapillarisierungszeit, die Temperatur des Transplantats, die Farbe der Haut und eine Blutung nach Punktion sind einfach zu erhebende und aussagekräftige Hilfen im postoperativen Lappen-Monitoring, erlauben jedoch keine detaillierte topographische Darstellung der Durchblutungssituation. Objektive und kontinuierliche Techniken wie die Pulsoxymetrie [28], Laser-Doppler-Flowmetrie [10,29], die Messung der Partialdrücke von O 2 und CO 2 [11,16,17], Temperaturmessung [3, 15,18] und andere Verfahren sind experimentell untersucht worden und haben nur an wenigen Abteilungen den Weg in die Klinik gefunden. Einige der Methoden erlauben bis zu einem gewissen Grad auch eine topographische Darstellung der Durchblutung, sind jedoch nur eingeschränkt zur Vorhersage der Nekroseentwicklung fähig.…”
Section: Introductionunclassified